Wear and corrosion resistance of CrN/TiN superlattice coatings deposited by a combined deep oscillation magnetron sputtering and pulsed dc magnetron sputtering - Ou, Y.X.; Lin, J.; Tong, S.; Che, H.L.; Sproul, W.D.; Lei, M.K. (Applied surface science, 2015)
•Combined deep oscillation magnetron sputtering deposited CrN/TiN coatings.•CrN/TiN coatings have a single fcc structure at various negative substrate bias.•H/E* and H3/E*2 ratios and LC in scratch tests depend on negative substrate bias.•CrN/TiN coatings exhibit a combined improvement in wear and corrosion resistance.•Wear resistance is related to high H/E* and H3/E*2 ratios and stress-related LC3. Deep oscillation magnetron sputtering (DOMS) is a novel high power impulse magnetron sputtering technique, which offers large voltage oscillation packets to generate a stable high-power discharge plasma with high ionization under virtually arc-free conditions. CrN/TiN superlattice coatings were deposited using a combined DOMS and pulsed dc magnetron sputtering (PDCMS) in a closed field unbalanced magnetron sputtering configuration. The Cr target was powered at 400W by DOMS and Ti target was powered at 2000W by PDCMS. The negative substrate bias (Vs) ranged from 0V to −100V. As the Vs was increased, CrN/TiN superlattice coatings showed a single phase face-centered cubic structure with a strong (111) texture. Correspondingly, the coatings exhibited the dense microstructure with well-defined interfaces between CrN and TiN layers. The increase in Vs led to a decrease in grain size and an increase in the compressive residual stress. The hardness and Young's modulus of the coatings increased with increasing Vs. The H/E* and H3/E*2 ratios and critical loads LC in scratch test showed an initial increase, followed by a decrease. The wear mechanism changed from severe adhesion wear to abrasion wear. The coating deposited at Vs=−60V exhibited mild abrasion wear with the lowest friction coefficient of 0.27 and the lowest specific wear rate of 0.5×10−6mm3N−1m−1 due to high hardness, H/E* and H3/E*2 ratios, LC1 and LC3 of 36GPa, 0.094, 0.316, 15.3N and 24N, respectively. The coatings also exhibited increasing pitting corrosion resistance with lower current density and higher corrosion potential in 3.5wt% NaCl aqueous solution. Combined DOMS+PDCMS techniques can provide the engineering surfaces for the industrial applications with the combined improvement in wear and corrosion resistance.